Does Perisaccadic Compression Require Foveal Vision?. (November 2014) - Matziridi, Maria; Hartendorp, Mijke O; Brenner, Eli; Smeets, Jeroen B J
People make systematic errors when localizing a stimulus that is presented briefly near the time of a saccade. These errors have been interpreted as compression towards the position that is fixated after the saccade. Normally, fixating a position means that its image falls on the fovea. Macular degeneration (MD) damages the central retina, obliterating foveal vision. Many people with MD adopt a new retinal locus for fixation, called the preferred retinal locus (PRL). If the compression of space during the saccade is a special characteristic of the fovea, possibly due to the high density of cones that is found in the fovea, one might expect people lacking central vision to show no compression of space around the time of a saccade. If the compression of space during the saccade is related to the position that is fixated after the saccade, one would expect compression towards the PRL, despite the lack of a high density of cones in this area. We found that a person with MD showed a clear compression towards her PRL. We conclude that perisaccadic compression is related to the position that is fixated after the saccade rather than to the high density of receptors in the fovea.